Microscopic Study of Bovine Serum Albumin Adsorption on Zinc Oxide (0001) Surface. Issue 6 (17th March 2021) - Rezek, Bohuslav; Hematian, Hadi; Jíra, Jaroslav; Rutherford, David; Kuliček, Jaroslav; Ukraintsev, Egor; Remeš, Zdeněk
Abstract : Bovine Serum Albumin Atomic model of bovine serum albumin (BSA) molecule adsorbed on polar (0001) Zn‐face surface of ZnO as calculated by force field simulations. It is overlaid by a 3D morphology of BSA layer on ZnO measured by atomic force microscopy (AFM). Increasing AFM force leads to compression and then scraping of BSA. More details can be found in article number 2000558 by Bohuslav Rezek and co‐workers.